Utilization of beet tops as affected by different storage methods - Heidebrecht, A. Allen, author; Washburn, L. E., advisor; Tom, R. C., committee member; Frey, Paul Reheard, committee member (Colorado State University. Libraries, 1943)
To view the abstract, please see the full text of the document.
Keywords: Feeds; Sugar beet